Correlation between ECG Changes and Coronary Angiographic Findings in Patient with Inferior Myocardial Infarction in a Tertiary Care Hospital - Haque, Shaikh Md. Shahidul; Ahsan, Mohammad Morshedul; Sarker, Alok Chandra; Hossain, Md. Shahadat; Kabir, Md. Shahriar; Jamil, Abu Baqar Md. (Cardiology and Cardiovascular Medicine, 2023)
Background: In patients with coronary artery disease, abnormalities in 12 leads Electrocardiography (ECG) are often used to localize the anatomic site of myocardial infarction and ischemia. The same ECG findings are often used to corelate with anatomy of coronary arteries and as well as the site of occlusion. The determination of infarct related artery in acute inferior MI is extremely important for prediction of amount of myocardium at risk and guide decisions regarding urgency of revascularization which might have positive impact on mortality and morbidity. But we do not have enough research-based information regarding the correlation of ECG changes with CAG findings in acute inferior myocardial infarction. Aim of the Study: Our objective of the study was to identify the infarct related artery either right coronary artery (RCA) or left circumflex artery (LCX) in acute inferior myocardial infarction using ECG criteria and comparing with coronary angiographic findings. Methods: The prospective observational study was conducted in the department of Cardiology, Shaheed Ziaur Rahman Medical College & Hospital, Bogura, Bangladesh during the period from July 2020 to June 2022. In total 185 patients with acute inferior myocardial infarction by ECG criteria were enrolled in this study as the study subjects. The ECG of these patients evaluated for significant ST segment elevation in inferior leads and comparing the ST elevation of lead III exceeding in Lead II plus ST segment depression >1 mm in lead aVL as a prediction of right coronary artery occlusion. If criteria were negative, LCX occlusion was likely. Proper written consent was taken from all the participants before data collection. For all the participants, either symptomatic or silent coronary angiography (CAG) was done within 4-6 weeks after an event to identify the culprit artery and also to see the non-culprit artery. Then ECG changes in various leads were used to localize the vessels involve and were correlated with dominant vessels involved in coronary angiography in development of inferior MI. All data were processed, analyzed and disseminated by using MS excel and SPSS version 23 program as per necessity. Results: The study population consists of 185 patients (152 male and 33 female) with mean ± SD age of 48.45 ±13.79 years. Among our participants, IRA disease burden were found 90%; in 70% RCA and in the rest 20% LCX were the culprit artery. On the other hand, non-IRA burden was 63%. In this study, as per the angiographic findings among our participants we observed that, cases with RCA, ‘RCA + LCX’, and ‘LAD + RCA + LCX’ were found in 20%, 23% and 28% respectively which were remarkable. Besides these, cases with LCX, ‘LAD + RCA’, ‘LAD + LCX’ and LM (Only) were found 5%, 8%, another 5% and 3% respectively whereas cases with normal vessels were found 10%. Finally, in assessing the vessel involvement we found DVD in more than one third (35%) of total patients. Besides this, cases with SVD and TVD were found in 28% and 26% respectively. Conclusion: It is possible to predict the culprit artery whether right coronary artery or left circumflex artery by examining the surface electrocardiography in patient with inferior myocardial infarction. A higher ST segment elevation in lead III than in lead II and deeper ST segment depression in aVL of surface ECG is the most useful parameters for predicting the RCA culprit artery in acute inferior wall myocardial infarction.